Micro/Nano Hierarchical Platforms: Carbon‐Nanogold Hierarchical Micro/Nano Topographies for Cell Guidance (Adv. Mater. Interfaces 22/2020). Issue 22 (20th November 2020) - Chauhan, Gaurav; Lujambio Ángeles, Alejandro; Gonzalez‐González, Everardo; Kulkarni, Manish M; Trujillo‐de Santiago, Grissel; Alvarez, Mario M.; Madou, Marc; Martinez‐Chapa, Sergio O.
Abstract : In article number 2000913, Marc Madou, Sergio O. Martinez‐Chapa and co‐workers fabricated carbon‐gold micro/nano hierarchical platforms using stimuli‐responsive wrinkling technology, utilizing the generation of depth wise photo‐crosslinking gradient in SU8 thin films doped with an ultraviolet light absorbing gold precursor. With micro/nano topological cues these surfaces have shown to be a promising 2½ dimensional cell scaffolds with the advantage of cell guidance for tissue engineering and lab/organ‐on‐a‐chip based applications.